Epididymal sperm quality of buffelous with Different Spotted Types - Y, Yulnawati; M, Rizal; H, Maheshwari; RR, Noor; C, Sumantri; A, Boediono (Indonesian Journal of Animal and Veterinary Sciences, 2013)
The significant decline of spotted buffalo population nowadays brought this species into an endangered situation. To perform an integrated conservation project, we need some basic information and data related to the reproductive and genetics potency of this buffalo. The purpose of this study was to observe the effect of coat color variation to the sperm quality, in order to get focus on specific candidate gene that allegedly bring the causative mutation(s) and responsible for the different pigmentation expression. In this study, we compare the quality of fresh and frozen-thawed epididymal sperm from 12 spotted bulls (that classified in 3 different spotted types, i.e Saleko, Bonga, and Lotong Boko) with five solid bulls. The results showed that there were no significant differences (P > 0.05) in all parameters of fresh and frozen-thawed epididymal sperm among those groups. The percentage of frozen-thawed progressive motility from Saleko, Bonga, Lotong Boko, and Solid was 44%, 42%, 40% and 42%, respectively. Moreover, the percentage of livability and membrane integrity of frozen-thawed sperm from each groups were 64.9%; 65.2%; 62.6%; 62.7% and 64.6%; 67.1%; 64.5%; 64.1%. In conclusion, it suggested that the coat color/phenotype difference has no effects on the quality of fresh and frozen-thawed epididymal sperm of spotted buffalo. Key Words: Epididymal Sperm, Spotted Buffalo